Trends in Mobile Medical Thermography - Ricardo Vardasca, PhD, ASIS, FRPS (2013)
The usage of computational systems in medicine is changing from traditional computers to mobile devices with high performance wireless network connections and high definition touch screen user interface. Medical imaging like other clinical information systems, follow that paradigm. Although Medical thermography is the second oldest modality of medical imaging, it has been disregarded for years. However recent technological improvements and the definition of standard capture protocols raised the interest in its usage in recent years. It is presented in this article the requirements that future medical thermography applications should include to be successful in common clinical practice.